Malaysian ESL teachers' attitude and challenges towards communicative language teaching / Siti Nurhidayah Nasir - Nasir, Siti Nurhidayah (2014)
Communicative Language Teaching (CLT) is known as teaching practices that develop learners' abilities to communicate in a second language. It indicates a change of focus in language teaching from linguistic structure towards developing second language learners’ abilities to communicate in the second language. Recently, many English as Second Language Learning (ESL) classrooms have adopted CLT into their curricula. However, the practices of CLT have faced various challenges in the ESL context. Thus, this study is driven by previous literature review highlighted that teachers' attitudes play a crucial role in revealing their thinking about CLT and their implementation of CLT. Theory of Reasoned Action (TRA) is used as theoretical framework of attitude to identify the attitudes of the teachers in implementing Communicative Language Teaching (CLT) approach. The study also aims to identify the challenges faced by the teachers that affect their intention to practice the CLT approach. Four research questions were constructed to help achieve the aims of this study and the research questions are: 1) what is the frequency of CLT approach practice by Malaysian ESL teachers in their teaching? 2) What are the Malaysian ESL teachers’ attitudes towards the CLT approach? 3) What are the challenges faced by Malaysian ESL teachers on CLT approach? And 4) what are the strategies adopted by Malaysian ESL teachers to overcome the challenges in implementing CLT in English class? The study utilized a mixed method research design as both quantitative and qualitative methods were applied. The quantitative data were obtained through the distribution of 100 questionnaires to ESL public school teachers in Shah Alam. 100 questionnaires were distributed and only 80 were returned and were selected for data analysis. The qualitative data were acquired through the interviews conducted to 8 English teachers in order to further explain and support the quantitative findings. The result from both quantitative and qualitative data suggested that the Malaysian ESL teachers implemented the CLT approach in the classroom. Moreover, Malaysian ESL teachers also prefer to conduct group discussion and pair work as an activity in teaching the English language. However, there is inconsistency in the selection of teaching materials between the respondents in quantitative study and qualitative study in which the respondents in quantitative study prefer the textbooks as the teaching materials as compared to authentic teaching materials. The result shows Malaysian ESL teachers have a positive attitude toward the CLT approach due to its benefits to promote self-directed learners as the role of the teacher in the CLT approach is no longer the authority but the transmitter of the knowledge in assisting students learning process. It is also highlighted on the challenges faced pertaining to the students’ attitude in the CLT classroom, the students’ learning style, the number of students in a class, and lack of school facilities in assisting the CLT lesson. Therefore, teaching strategies such as the use of extrinsic motivation (encouragement and class punishment) is used by the teachers to overcome the challenges they faced in implementing the CLT approach in the Malaysian classroom. The implication of the study indicates that the Malaysian English teachers choose to practice the CLT approach in teaching the second language. This result is contradicted with the previous research that suggested that Malaysian ESL teachers prefer to practice traditional approach as compared to CLT. However, the challenges pertaining to students’ attitude, participation and achievement in the classroom can affect teachers’ attitudes towards the practice of CLT approach. As recommendation for future research, it is suggested that more research to be conducted to investigate the content of Malaysian English textbooks as suitable teaching material to the CLT approach. Moreover, it is suggested that more research to be conducted based on the role of grammar teaching in the CLT approach. Lastly, it is recommended that a broader study related to teachers’ and students’ attitude towards the practice of CLT approach to be conducted in the future.